Crossing Languages to Play with Words Multidisciplinary Perspectives - Knospe, Sebastian 1979-; Onysko, Alexander 1974- (The Dynamics of Wordplay, 2016)
Wordplay involving several linguistic codes represents an important modality of ludic language. It is attested in different epochs, communicative situations, genres, and contexts of use. The translation of wordplay, which is generally seen as a challenging enterprise, illustrates another dimension of crossing linguistic borders in wordplay. The third volume of the series The Dynamics of Wordplay unites contributions from different disciplines which study the creative and playful use of elements from different languages and the transfer of ludic language into other linguistic systems. It sheds light on the multi-dimensionality, special linguistic make-up, and specific interactive potential of wordplay at the interface of different languages and cultures. The individual studies collected in this volume will be of interest to scholars from different scientific fields, such as linguistics and literary studies as well as cultural and media studies